Episcopal Appointments in England, c. 1214-1344 From Episcopal Election to Papal Provision. - Harvey, Katherine (Farnham : Ashgate Publishing Ltd, 2014)
Bishops were central figures in medieval society and the circumstances of their appointments are of great historical importance. This book considers the theory and practice of free canonical election in its heyday under Henry III and Edward I, and the nature of and reasons for the subsequent transition to papal provision. An analysis of the theoretical evidence for this subject (including canon law, royal pronouncements and Lawrence of Somercote's remarkable 1254 tract on episcopal elections) is combined with a consideration of the means by which bishops were created during the reigns of Henry.
Cover; Contents; Figures and Tables; Acknowledgements; Abbreviations; Introduction; Part I The Age of Election; 1 The Theory of Election; 2 The Custom of Election: Ritual and Finance; 3 The Practice and Problems of Episcopal Election, c.1214-c.1307; Part II The Age of Provision; 4 The Age of Provision: Canon Law and Custom; 5 The Age of Provision: Responses and Consequences; Part III The European Context; 6 Episcopal Appointments in a European Context; Conclusion; Appendix: Appointments to English Bishoprics, 1215-1344; Bibliography; Index.
Description based on print version record.
Keywords: Bishops -- Appointment, call, and election -- History; Clergy -- Appointment, call, and election -- History; Election law (Canon law); Great Britain -- Church history -- 1066-1485.; Bishops -- Appointment, call, and election -- History; Clergy -- Appointment, call, and election -- History; Election law (Canon law); Great Britain -- Church history -- 1066-1485.; RELIGION / Christian Theology / Ecclesiology; Electronic books